Enhanced Obstacle Contrast to Promote Visual Scanning in Fallers with Parkinson's Disease: Role of Executive Function. (1st June 2020) - Alcock, Lisa; Galna, Brook; Hausdorff, Jeffrey M.; Lord, Sue; Rochester, Lynn
Highlights: PD approached the low contrast obstacle slower than controls. PD spent longer looking at the obstacle compared to controls regardless of contrast. PD looked at the ground beyond the low contrast obstacle less than controls. Gaze location was associated with executive function and not visual function in PD. Enhancing obstacle contrast may improve online processing of environmental cues. Abstract: The ability to perceive differences in environmental contrast is critical for navigating complex environments safely. People with Parkinson's disease (PD) report a multitude of visual and cognitive deficits which may impede safe obstacle negotiation and increase fall risk. Enhancing obstacle contrast may influence the content of visual information acquired within complex environments and thus target environmental fall risk factors. 17 PD with a history of falls and 18 controls walked over an obstacle covered in a high and low contrast material in separate trials whilst eye movements were recorded. Measures of visual function and cognition were obtained. Gaze location was extracted during the approach phase. PD spent longer looking at the obstacle compared to controls regardless of contrast ( p  < .05), however group differences were largest for the low contrast obstacle. When accounting for group differences in approach time, PD spent longer looking at the low contrast obstacle and less time looking at the ground beyond the low contrast obstacle compared to controls ( p  < .05). The response to obstacle contrast in PD (high-low) was significantly associated with executive function. Better executive function was associated with spending longer looking at the low contrast obstacle and at the ground beyond the high contrast obstacle. Enhancing the contrast of ground-based trip hazards may improve visual processing of environmental cues in PD, particularly for individuals with better executive function. Manipulating contrast to attract visual attention is already in use in the public domain, however its utility for reducing fall risk in PD is yet to be formally tested in habitual settings.